Prohibiting Use of Recreational Cannabis by Safety-Sensitive Workers in Canada : A Legal Evaluation of the New Workplace Policies - Walsworth, Scott (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2021)
AbstractIn 2018, Canada became the first G7 nation to legalize recreational cannabis. In response, at least a dozen prominent employers in safety-sensitive industries implemented policies to prevent workers from using legal cannabis for extended periods before reporting for duty, ranging from 28 days to a continual ban. The various unions that represent these workers allege an unnecessary breach of employee privacy and intend to challenge the legality of the policies. Informed by labour arbitration and Supreme Court decisions, this paper proposes a custom-made test and uses it to assess the enforceability of the new cannabis workplace policies. Notwithstanding the significant challenges facing employers, it is the position of this paper that the new policies are enforceable under certain conditions. SummaryInformed by labour arbitration and Supreme Court decisions, this paper proposes a custom-made test and uses it to assess the enforceability of the new cannabis workplace policies, which prohibit legal consumption for safety-sensitive workers. The analysis identifies two main challenges facing employers.Establishing that a problem exists in the workplace. Consumption of cannabis must have an impairing effect during the period of prohibition. Demonstrating that the policy has sufficient benefits to justify the consequences. The improvements in workplace safety must outweigh the breech of employee privacy.To identify a problem in the workplace, employers will rely on the strongest available evidence linking cannabis to impairment during the entire period of prohibited consumption. Medical research is helpful in this regard. A substantial body of evidence points to significant motor and cognitive deficiencies immediately following consumption (first eight hours). Although some studies indicate a prolonged period of impairment, the evidence is less compelling as a user approaches 30 days of abstinence. At the same time, employers must contend with the difficulty of establishing the benefits of a workplace policy that relies on existing cannabis testing technology and which, at best, identifies an unspecified level of consumption at some time during the preceding 30 days.The employer thus faces a conundrum. On the one hand, the period of prohibited consumption can be shortened to align with current scientific evidence on the length of impairment. The policy will then be more difficult to enforce because existing testing technology cannot prove that the consumption took place during the shorter period. On the other hand, the period can be lengthened to 30 days to align with the limitations of existing testing technology. The policy will then be criticized because the longer period is not justified by current scientific evidence. Notwithstanding the significant challenges facing employers who pursue either option, it is the position of this paper that the policies are defendable under certain conditions.